IMPROVING UNDERSTANDING AND MATHEMATICAL COMMUNICATION LEVEL AND STUDY LEARNING WITH RECIPROCAL TEACHING APPROACH - Iis Yuniar; Euis Eti Rohaeti; R Bambang Aryan Soekisno ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This research is to analyze and analyze the improvement and achievement of students' understanding and communication ability and the independence of junior high school students learning using Reciprocal Teaching approach compared to using ordinary learning. The population in this study is the seventh-grade students of SMP in one school in Bandung. The sample of the experimental class and the control class. The method used in this research is quasi-experiment. Data processing of communication skills and mathematical understanding using a t-test, two-lane ANOVA, and linear regression. The result of the research shows that the achievement and improvement of students' mathematical understanding and communication ability which get the learning using the Reciprocal Teaching approach are better than the students who get regular learning. Students of experimental class with Reciprocal Teaching learning and control class with ordinary learning there is no relation between mathematical understanding ability with student learning independence and experimental class students with Reciprocal Teaching lesson and control class with ordinary learning there is no correlation between mathematical communication ability with student learning independence.